A comparative study of titanium elastic nailing and plate osteosynthesis for pediatric both-bone diaphyseal forearm fractures - Patra, Gopabandhu; Prusty, Alok; Sahu, Anil Kumar (International Journal of Research in Orthopaedics, 2026)
Background: Both-bone diaphyseal forearm fractures are common in children and require stable fixation for optimal functional recovery. Plate osteosynthesis (PO) and titanium elastic nailing (TEN) are widely used surgical techniques. Comparative evidence on outcomes between these methods remains limited. Methods: This multicentric, comparative study included 70 children aged 5-15 years with diaphyseal both-bone forearm fractures. Thirty-five patients underwent PO and 35 underwent TEN. Functional outcomes were assessed using the price criteria, and radiological union and radial bow restoration were evaluated. Operative duration, hospital stay, and complications were also recorded. Results: Operative time and hospital stay were significantly shorter in the TEN group compared to PO. Functional outcomes were predominantly excellent in both groups, with no significant difference. Radiological union times and restoration of radial bow were comparable between groups. Complication rates were low and similar in both groups. Conclusions: TEN provides equivalent functional and radiological outcomes to PO, with shorter surgery and hospitalization.